기후변화 대응을 위한 EU 탄소국경조정메커니즘(CBAM)의 경제적 효과 분석 - 윤승환(Seung-Hwan Yoon) (무역연구, 2022)
Purpose – Countries around the world are focusing policy efforts on combating climate change and promoting long-term economic recovery, and major greenhouse gas emitting countries are joining the carbon neutrality declaration. To address the risk of carbon leakage, the EU introduced the CBAM(Carbon Border Adjustment Mechanism) in July 2021. The purpose of this study is to examine the potential economic effects of the CBAM on its major trading partners, including Korea, and to draw implications. Design/Methodology/Approach – Using a global, multisector, computable-general-equilibrium model and GTAP database Version 10A, this paper undertakes to assess the potential economic impacts of the CBAM. The baseline scenario was set up using the World Bank's macroeconomic data, such as real GDP, population, labor, and capital from 2015 to 2020 to calculate future estimates. Policy scenarios were established by (1) imposing 30 euros per ton of embedded emissions in the total amount of imports, (2) imposing 30 euros per ton of embedded emissions on five products covered by the CBAM in the European Commission’s July 2021 proposal, (3) imposing 30 euros per ton of CO contained in items that are subject to additional duties, and (4) lastly, the above scenarios 2 and 3 were combined to see the total effects of the CBAM. Findings – Simulation results showed that in the case of Scenario 1, wherein tariffs were imposed depending on CO emissions, intra-regional trade and production increased, resulting in a significant growth in consumer welfare in the EU (approximately $12.1 billion). Except for Japan, all major trading partners decreased overall, although there were disparities in size. In particular, China (about $10.9 billion), Russia (about $ 7.1 billion), and India (about $4.2 billion) reported significant drops in consumer welfare. Korea has exported an annual average of about $53.7 billion to the EU for the past six years, with items subject to the CBAM accounting for around $4.17 billion, or 7.8% of total exports. Of these items, iron and steel with a value of about $3.65 billion, accounting for about 87.3% of the total should be a source of concern for the Korean government and the steel industry. According to findings, the steel industry’s exports to the EU are likely to drop by 0.99 percent, resulting in a loss of nearly 310 million euros in exports (about 360 million US dollars). Research Implications – This study is meaningful in that it provides reference data to Korean industries that can be directly affected by the CBAM, which has already been introduced and is about to be implemented. For some export industries like the steel industry, in particular, it is necessary for the Korean government to actively support low-carbon technology innovation and accelerate the transition to a low-carbon economy. KCI Citation Count: 3